Laser beam modulation by an acousto optic mode locker - Mat Daud, Nazariah; Saidin, Mohamad Khairi; Bidin, Noriah; Mat Daud, Yaacob (Faculty of Science, University Teknologi Malaysia, 2006)
Nazariahmatdaud2006the characterization of beam modulation by acousto-optic mode locker is reported. Hene laser was employed as a source. Acousto-optic mode locker (aoml) was used to convert the continuous beam to become pulsed. Radio frequency signal provided an acoustic source to the aoml. The signal was amplified using a power amplifier. A pulse generator was utilized to regulate the frequency of the signal. The frequency and the power of the amplifier were varied to characterize the modulated beam. The hene laser beam was modulated into a periodic signal. The pulse width of the modulated signal was found to increase linearly with the rf pulse width. The modulated signal intensity was also found to vary linearly with rf drive power_laserbeammodulationbyan